Adenosine A2A Receptor Blockade Modulates Glucocorticoid-Induced Morphological Alterations in Axons, But Not in Dendrites, of Hippocampal Neurons - Pinheiro, Helena; Gaspar, Rita; Baptista, Filipa I.; Fontes-Ribeiro, Carlos A.; Ambrósio, António F.; Gomes, Catarina A. (Frontiers in Pharmacology, 2018)
The exposure to supra-physiological levels of glucocorticoids in prenatal life can lead to a long-term impact in brain cytoarchitecture, increasing the susceptibility to neuropsychiatric disorders. Dexamethasone, an exogenous glucocorticoid widely used in pregnant women in risk of preterm delivery, is associated with higher rates of neuropsychiatric conditions throughout life of the descendants. In animal models, prenatal dexamethasone exposure leads to anxious-like behaviour and increased susceptibility to depressive-like behaviour in adulthood, concomitant with alterations in neuronal morphology in brain regions implicated in the control of emotions and mood. The pharmacologic blockade of the purinergic adenosine A2A receptor, which was previously described as anxiolytic, is also able to modulate neuronal morphology, namely in the hippocampus. Additionally, recent observations point to an interaction between glucocorticoid receptors and adenosine A2A receptors. In this work, we explored the impact of dexamethasone on neuronal morphology, and the putative implication of adenosine A2A receptor in the mediation of dexamethasone effects. We report that in vitro hippocampal neurons exposed to dexamethasone (250 nM), in the early phases of development, exhibit a polarized morphology alteration: dendritic atrophy and axonal hypertrophy. While the effect of dexamethasone in the axon is dependent on the activation of adenosine A2A receptor, the effect in the dendrites relies on the activation of glucocorticoid receptors, regardless of the activation of adenosine A2A receptor. These results support the hypothesis of the interaction between glucocorticoid receptors and adenosine A2A receptors and the potential therapeutic value of modulating adenosine A2A receptors activation in order to prevent glucocorticoid-induced alterations in developing neurons.